2017
DOI: 10.17140/droj-3-129
|View full text |Cite
|
Sign up to set email alerts
|

Ketone Body Production and Excretion During Wellness Fasting

Abstract: Introduction : The importance of ketone body metabolism in diabetic patients has been known since the 1970s, but recently β-hydroxybutyrate (βHB) has been identified as a key component of a metabolic signaling pathway. However, many questions remain unanswered about individual differences in the production and excretion of ketone bodies. Objectives: Fourteen healthy subjects were admitted in the ARSOA Wellness Fasting program. During a 4-day fasting period, they received a combination of very low-energy veget… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…It could be due to low caloric food consumption due to severe nausea and vomiting which could have result to weight loss in hyperemesis gravidarum cases. 18,19 A Study conducted by Watanabe S et al 20 obtained decreased blood glucose level in fasting state.…”
Section: Discussionmentioning
confidence: 99%
“…It could be due to low caloric food consumption due to severe nausea and vomiting which could have result to weight loss in hyperemesis gravidarum cases. 18,19 A Study conducted by Watanabe S et al 20 obtained decreased blood glucose level in fasting state.…”
Section: Discussionmentioning
confidence: 99%
“…Continuing Super-LCD usually makes the patient elevated ketone bodies and significant weight reduction [13,15,16]. Continuing ketogenic diet seems to be necessary to obtain enough weight reduction [17][18][19]. Furthermore, the ratio of carbohydrate in LCD showed correlation with the degree of weight reduction [20].…”
Section: Discussionmentioning
confidence: 99%
“…In ARSOA Wellness Fasting 4 days program, participants received a combination of the very low-energy vegetarian diet, physical exercise, meditation, and lectures about healthy lifestyles [7,9]. (Figure 1) Data were collected from October 2014 to October 2018.…”
Section: Methodsmentioning
confidence: 99%
“…We have practiced Kushi macrobiotics for more than 10 years and developed the teaching and practicing system of a 4-day "Wellness-fasting" [7][8][9]. Our previous study in wellness fasting and BHB production by PASS analysis showed that the decreased BMR and insulin significantly contributed to the increase in BHB and acetyl acetate (AcAc) [9]. In this paper, we would like to focus on the changes in blood pressure in conjunction with other physical markers during wellness fasting.…”
mentioning
confidence: 99%